SEISMICITY ANALYSIS BASED ON THE INTEGRATION OF EARTHQUAKE VULNERABILITY INDEX (KG) THROUGH POLYGON DISTRIBUTION IN BENGKULU CITY AREA - Shela Purba; Refrizon; Arif Ismul Hadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Bengkulu Province is an area with a very high level of earthquake susceptibility, this is due to the confluence of large tectonic plates, covering Indo-Australia, Eurasia, and the Pacific. This is the fundamental reason for the need for micro-zoning mapping as a basis for spatial planning evaluation and sustainable development, especially in the city of Bengkulu which is the heart of the province where it is the center of regional social and economic activities. This concept is by applying the Horizontal to Vertical Spectral Ratio (HVSR) method and inversion of the microtremor curve as a result of obtaining shear wave velocity data at a depth of 30 meters as many as 30 measurement points covering the distributed Bengkulu City that forms polygons. The HVSR parameters reviewed include dominant frequency (f₀), amplification (A₀), and seismic vulnerability index ( Kg) show that Bengkulu City has very heterogeneous sediment characteristics from soft to hard where the value of the earthquake susceptibility index is in the range of 0.25-8 and the shear wave speed range at a depth of 30 meters, namely in the range of 240 m/s - 520 m/s. This study concludes that Bengkulu City has a very complex level of seismic vulnerability with specific conditions that divide the area into 3 large zones which include the risk zone, conditional zone, and safe zone. The division of the zone is an illustration of the response behavior to the area in Bengkulu City, both actions of managing the area wisely through improving the design of earthquake-resistant building structures so that the basis of regional planning recommendations for the direction of spatial planning in Bengkulu Province can minimize disaster risk. Keywords: HVSR, Microtremor, Vs30, Earthquake vulnerability index, Microzoning, spatial planning.